Association between blood glucose level with glycemic load, physical activity and compliance to medication among Diabetes Mellitus (DM) patients in Buleleng District General Hospital, Bali Province - Ketut Adi Jaya Sutana; Komang Ayu Kartika Sari; I Wayan Weta; Ketut Suastika (Public Health and Preventive Medicine Archive, 2017)
Background and purpose: The prevalence of diabetes mellitus (DM) in Indonesia is increasing, including in Buleleng District, Bali Province. Studies regarding determinants of blood glucose control in DM patients show varied findings. This study aims to examine association between blood glucose level with physical activity, compliance to medication and glycemic load among DM patients. Methods: A cross-sectional survey was conducted in Buleleng District General Hospital from March to April 2017. A total of 73 patients were concecutively recruited to participate in our study. Data were collected through interview, observation and measurement. Data collected included socio-demographic characteristics, fasting blood glucose level, 1-hour and 2-hour postprandial blood glucose levels, carbohydrate intake, body mass index, glycemic index, glycemic load, physical activity, genetic or family history, and compliance to medication. A bivariate analysis was performed to examine association between independent variables and blood glucose levels. Multivariate analysis was also conducted to calculate adjusted odd ratio using a binary logistic regression. Results: Our study found that blood glucose levels of most respondents were relatively well managed–63% for fasting, 61.6% for 1-hour postprandial, and 63% for 2-hours postprandial. Multivariate analysis revealed that fasting blood glucose level were associated with regular physical activities (AOR=74.09; 95%CI: 7.52-729.69) and compliance to medication (AOR=11.90; 95%CI: 2.24-63.29). Furthermore, 1-hour postprandial blood glucose level were associated with breakfast glycemic load (AOR=0.63; 95%CI: 0.47-0.85) and compliance to medication (AOR=27.29; 95%CI: 2.29-323.95), while 2-hour postprandial blood glucose level were associated with breakfast glycemic load (AOR=0.69; 95%CI: 0.54-0.89) and compliance to medication (AOR=19.81; 95%CI: 2.31-170.14). Conclusions: Factors associated with fasting blood glucose level were regular physical activities and adherence to medication, while 1-hour and 2-hours postprandial blood glucose levels were both influenced by breakfast glycemic load and compliance to medication.